Prospects and problems of implementation research on soil transmitted helminthes (STHs) infection in Bangladesh - Tilak Chandra Nath (Berita Kedokteran Masyarakat (BKM), 2018)
Soil-transmitted helminths are responsible for diseases that thrive where there is poverty and disadvantage. Although rarely fatal, it is recognized as a leading global cause of lifelong disability. To achieve the target set by World Health Assembly, efforts must be intensified to eliminate STH as a public-health problem. Accumulated scientific knowledge and the availability of safe anthelminthics such as mebendazole and albendazole laid the foundation for a global strategy to control STH. However, there are several foreseeable challenges and risks to the success of an MDA-based transmission interruption strategy for STH. Continued progress toward global STH elimination will require solutions to potential obstacles in the most challenging— that is, the poorest—endemic settings like Bangladesh.